The complete mitochondrial genome of Vaccinium oldhamii Miquel, a plant of the Ericaceae family - Da Hyun Lee; Woo Hyun Sim; Chung Youl Park; Do Hyun Kim; Jun Hyeok Kim; Hyeon Min Kim; Sang Hoon Che; Wan Geun Park; Chae Sun Na; Sangrea Shim (Mitochondrial DNA. Part B. Resources)
Vaccinium oldhamii Miquel 1866 is a deciduous shrub native to Northeast Asia, including Korea, China, and Japan. Its polyphenol-rich edible berries may aid in managing chronic diseases. Despite its importance, the mitogenome of this species remains understudied. This study assembled the complete mitogenome, consisting of 626,941 bp with 45.34% GC content, using NOVOPlasty and Illumina sequencing. The genome includes 38 protein-coding genes, 24 tRNA genes, and three rRNA genes. Phylogenetic analysis revealed a close relationship with V. macrocarpon. This mitogenome provides a valuable resource for phylogenomic studies and insights into evolutionary relationships within the Vaccinium genus and the Ericales order. Vaccinium oldhamii Miquel 1866 is a deciduous shrub in the Ericales and the Ericaceae and is native to Northeast Asia including Korea, China, and Japan. Particular emphasis has been placed on the edible berries of Vaccinium species and their use as dietary supplements. Specifically, the edible berries of V. oldhamii contain high levels of polyphenols, which may aid in preventing and managing chronic diseases. However, the mitogenome sequence of this species, a valuable resource for studying evolutionary relationships and genetic diversity within the Vaccinium genus, has not been thoroughly investigated. In this study, the complete mitochondrial genome sequence of V. oldhamii was assembled into 626,941 bp circular nucleotides with a GC content of 45.34% using NOVOPlasty and Illumina sequencing data. The comprehensive annotation for mitogenome of V. oldhamii revealed that the mitogenome comprises 38 known protein-coding genes, 24 tRNA genes, and three rRNA genes. Phylogenetic analysis using ML method showed that this species is closely related to the V. macrocarpon. This newly sequenced mitochondrial genome offers a valuable resource for phylogenomic analysis and will enhance our understanding of evolutionary relationships within the Ericales order and/or the Vaccinium genus.